Energy‐Resolved Mass Spectrometry as a Tool for Identification of Lignin Depolymerization Products. Issue 1 (16th November 2022) - Dong, Xueming; Mayes, Heather B.; Morreel, Kris; Katahira, Rui; Li, Yanding; Ralph, John; Black, Brenna A.; Beckham, Gregg T.
Abstract: Lignin is the largest source of bio‐based aromatic compounds in nature, and its valorization is essential to the sustainability of lignocellulosic biorefining. Characterizing lignin‐derived compounds remains challenging due to the heterogeneity of this biopolymer. Tandem mass spectrometry is a promising tool for lignin structural analytics, as fragmentation patterns of model compounds can be extrapolated to identify characteristic moieties in complex samples. This work extended previous resonance excitation‐type collision‐induced dissociation (CID) methods that identified lignin oligomers containing β–O–4, β–5, and β–β bonds, to also identify characteristics of 5–5, β–1, and 4–O–5 dimers, enabled by quadrupole time‐of‐flight (QTOF) CID with energy‐resolved mass spectrometry (ERMS). Overall, QTOF‐ERMS offers in‐depth structural information and could ultimately contribute to tools for high‐throughput lignin dimer identification. Abstract : A closer look : This work highlights the advantage of using quadrupole time‐of‐flight collision‐induced dissociation mass spectrometry (QTOF‐CID‐ERMS) at multiple accelerating potentials, as compared to performing CID‐MS/MS with a quadrupole ion trap (QIT). The former provides data‐rich fragmentation spectra, allowing distinction among six major lignin linkages, and can serve as a promising addition to the current lignin analytical toolbox.